Janet Frame : semiotics and biosemiotics in her early fiction - St. Pierre, Paul Matthew (Rowman & Litterfield Publishers, 2011)
"In Janet Frame: Semiotics and Biosemiotics in Her Early Fiction, Paul Matthew St. Pierre exploits the linguistic discipline of semiotics and the neurobiological discipline of biosemiotics to propose an original and dynamic reading of the first four works of fiction by New Zealand writer Janet Frame (1924-2004): The Lagoon: Stories (1951), Owls Do Cry (1957), Faces in the Water (1961), and The Edge of the Alphabet (1962). Opposing the prevailing reading of Frame's early fiction as autobiographical, deriving from her medical history, he argues her books are singular evocations of her astonishing imagination. His purpose is to fix this historical record and provide an alternative model for interpreting one of the 20th century's most stylistically demanding and rewarding writers. Semiotics and biosemiotics are his means for unlocking the early fiction and her later works to a polemical analysis focusing on language, sign transmissions, writing the body, and the biosemiotic self ..."--Publisher description.